Konsep Inyeon sebagai Wujud Determinisme dalam Film Past Lives - Nadira Malika Havishta; Annisa Luthfiarrahman; Eva Latifah (Universitas Gadjah Mada, 2026)
The concept of Inyeon in Korean philosophy reflects a spiritual connection involving causality between individuals, spanning both current and Past Lives. This study analyzes the representation of the Inyeon concept as a form of determinism in the film Past Lives (2023) by Celine Song, using a qualitative descriptive method and Jonathan Edwards' theory of determinism. The results identify two forms of determinism: causal determinism and theological determinism. Causal determinism highlights causal relationships grouped into three types: continuing, detaching, and shifting Inyeon. Meanwhile, theological determinism reflects a belief in predestined fate, classified into four types: accepting, resisting, appreciating, and regretting Inyeon. The results show that theological determinism is more dominant, emphasizing the film's narrative focus on belief in fate and reflections on human relationships. This study offers new insights into the relevance of the Inyeon concept in Korean culture and modern media.